ISLAMIYAH DAN RELEVANSINYA DI ERA KONTEMPORER: STUDI KITAB BIDAYAH WAN NIHAYAH - Muhamad Zainal Abidin; Rifqi Musaffa (Kuttab: Jurnal Ilmu Pendidikan Islam, 2025)
The Ukhuwah Islamiyah in Indonesia now has a lot of conflicts, even not a few of them attack each other both physically and non-physically, so more in-depth research is needed on solution that can deal with these divisions. This research aims to make readers better understand the strategies of Ali bin Abi Tholib in overcoming various conflicts of the ummah in his time,and their relevance in maintaining Islamic ukhuwah in this contemporary era. This study uses a library research method, by searching and analyzing books or data related to this research. This research finds some similarities between the conflicts of the ummah that occur today and the conflicts of the ummah that occurred in the time of Ali Bin Abi Tholib, so that some of the strategies used by Ali Bin Abi Tholib are relevant in this contemporary era.